PENGARUH KOMPETENSI, DISIPLIN DAN MOTIVASI GURU TERHADAP KINERJA GURU DI UNIT PELAKSANA TEKNIS SEKOLAH DASAR ( SD ) NEGERI 050627 PURWOBINANGUN KECAMATAN SEI BINGAI KABUPATEN LANGKAT - Deddy Surya Winata (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The problem formulation in this study is: How is competency towards teacher performance? , How is discipline to teacher performance? How does teacher motivation to teacher performance? How does the teacher's competency, discipline and motivation be simultaneous to the teacher's performance, the results of the research gained that there is a variable of competency positive and significant to the performance of Guru with the value of Thitung T table (5,249 1,664) and the value of significance (0.000 0.05). The discipline variables have a positive and significant effect on the master's performance with the value of Thitung T table (2,369 1,664) and the significance value (0.000 0.05). The motivation variable positively and significantly affects the teacher's performance with the value of Thitung T table (4,548 1,664) and value Significance (0.000 0.05) variable competence, discipline and motivation effect positive and significant towards Guru with Fcount value Ftable (29,228 2,712) and significance value (0.000 0.05). The influence of competency variables, discipline and motivation has positive and significant impact on the teacher at 75.80%, while the remaining amount is 24.20% (100%-75.80%) Influenced by other factors not researched.